Pengaruh Persepsi Nasabah dan Tingkat Margin terhadap Keputusan Nasabah Pembiayaan Murabahah di BSI KCP Bandung Geger Kalong - Siska Devi Amalia; Faisal Rakhman (Jurnal Dimamu, 2022)
The background of this research is that it is suspected that the customer's lack of understanding of the specified margin gives rise to the customer's perception that the margin applied to Islamic banks is the same as the interest applied to conventional banks. In addition, the level of margin that is considered high and not in accordance with the ability of the customer is also suspected of influencing the decisions of murabahah financing customers partial and simultaneous. The object of research in this report is the customer at Bank BSI KCP Bandung Geger Kalong. The method used is quantitative associative. The type of data used is primary data which is processed using statistical applications, and uses data collection techniques in the form of observations, interviews, questionnaires, and literature studies. The population in this study is murabahah financing customers in 2021 with a sample of 93 people. The results showed that there was a significant influence between customer perceptions of customer decisions on murabahah financing at BSI KCP Bandung Geger Kalong by 33.3% with t test results where the value of t count > t table (6,747>1,986), there was a significant influence between the level of margin on customer decisions on murabahah financing at BSI KCP Bandung Geger Kalong by 46.1% with the results of the t test where the value of tcount > ttable (8,819>1,986), and simultaneously there is a significant influence between customer perceptions and the level of margin on customer decisions on murabahah financing at BSI KCP Bandung Geger Kalong is 53.2% with F test results where F count > F table (51.154 > 3.10)